Pengembangan SOP dalam Meningkatkan Kualitas Pelayanan di Saung Angklung Udjo - Tanu Wijaya, Jonathan Bryant; Kemala, Zia (Manajemen dan Pariwisata, 2025)
Indonesia is a country rich in natural resources and cultural heritage, with the tourism sector being one of its major contributors to foreign exchange. In West Java, particularly in Bandung City, there is a well-known cultural and educational tourism destination, Saung Angklung Udjo. This study aims to analyze the implementation of Standard Operating Procedures (SOP) at Saung Angklung Udjo and to identify the obstacles encountered in their application. The research employs a qualitative method with data collection techniques including interviews, observations, and literature studies. The findings indicate, first, that there are twelve types of SOP implemented at Saung Angklung Udjo, which include SOPs for Art Performances, Education, Facility Management, Cultural Preservation, Products, Employees, Tour Guides, Visitors, Guest Services and Performances, Angklung Production and Maintenance, Marketing and Promotion, and Crisis Management. However, the implementation of these SOPs has not been optimal due to reliance on old work habits, direct instructions, and situational adjustments in the field. Second, several challenges in SOP implementation were identified, including limited socialization and compliance, insufficient evaluation and procedural updates, and constraints in human resources. This study is expected to provide insights and contributions to Saung Angklung Udjo in improving service quality and operational effectiveness, thereby supporting sustainability and professionalism in managing cultural tourism destinations.